DINAMIKA POLITIK PENGEMBANGAN MADRASAH: TANTANGAN DAN PELUANG MENGHADAPI PERSAINGAN GLOBAL - Syukur Penerangan Hasibuan; Zaianal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2024)
Madrasah is an Islamic educational institution, facing significant challenges in the era of global competition. The political dynamics that accompany the development of madrassas require a comprehensive study to understand the complexity of this institutional transformation process. This research aims to analyze the challenges and opportunities faced by madrasas in a global context, as well as explore effective development strategies. This study uses a qualitative approach to examine political dynamics in madrasah development and explore the challenges and opportunities it faces in global competition. The results of the study show that madrasas face the main challenges in quality standardization, curriculum relevance, competence of educators, and strengthening infrastructure. However, the global era also opens up opportunities for madrasas to integrate science with Islamic values, develop soft skills, and carry out international collaboration. Political dynamics in the development of madrassas involve complex negotiations between the demands of modernization and the preservation of Islamic identity. In conclusion, the development of madrassas in the face of global competition requires a holistic approach that considers political, social, and cultural dynamics. The success of madrasah transformation depends on the ability of stakeholders to manage challenges and strategically capitalize on opportunities. Madrasah has the unique potential to become an educational model that combines Islamic values with global competence, but its realization requires a clear vision and close collaboration between various parties.